Non-random escape pathways from a broadly neutralizing human monoclonal antibody map to a highly conserved region on the hepatitis C virus E2 glycoprotein encompassing amino acids 412-423. - Zhen-yong Keck; Allan G N Angus; Wenyan Wang; Patrick Lau; Yong Wang; Derek Gatherer; Arvind H Patel; Steven K H Foung (PLoS Pathogens)
A challenge for hepatitis C virus (HCV) vaccine development is to define epitopes that are able to elicit protective antibodies against this highly diverse virus. The E2 glycoprotein region located at residues 412-423 is conserved and antibodies to 412-423 have broadly neutralizing activities. However, an adaptive mutation, N417S, is associated with a glycan shift in a variant that cannot be neutralized by a murine but by human monoclonal antibodies (HMAbs) against 412-423. To determine whether HCV escapes from these antibodies, we analyzed variants that emerged when cell culture infectious HCV virions (HCVcc) were passaged under increasing concentrations of a specific HMAb, HC33.1. Multiple nonrandom escape pathways were identified. Two pathways occurred in the context of an N-glycan shift mutation at N417T. At low antibody concentrations, substitutions of two residues outside of the epitope, N434D and K610R, led to variants having improved in vitro viral fitness and reduced sensitivity to HC33.1 binding and neutralization. At moderate concentrations, a S419N mutation occurred within 412-423 in escape variants that have greatly reduced sensitivity to HC33.1 but compromised viral fitness. Importantly, the variants generated from these pathways differed in their stability. N434D and K610R-associated variants were stable and became dominant as the virions were passaged. The S419N mutation reverted back to N419S when immune pressure was reduced by removing HC33.1. At high antibody concentrations, a mutation at L413I was observed in variants that were resistant to HC33.1 neutralization. Collectively, the combination of multiple escape pathways enabled the virus to persist under a wide range of antibody concentrations. Moreover, these findings pose a different challenge to vaccine development beyond the identification of highly conserved epitopes. It will be necessary for a vaccine to induce high potency antibodies that prevent the formation of escape variants, which can co-exist with lower potency or levels of neutralizing activities.